NUANCES OF CHARACTER DISPOSITION REPRESENTING THEMES OF LOSS AND RECOVERY IN ANNE OF GREEN GABLES AND THE SECRET GARDEN (Journal of English Language and Literature Teaching, 2025)
The Nuances of Character Disposition in Representing Themes of Loss and Recovery has the objectives of: 1 to identify and describe the nuances of character disposition in representing themes of loss and recovery as depicted in Anne of Green Gables< em> by nbsp; Montgomery 1908 and The Secret Garden< em> by Burnett 1911 ; 2 to analyse and compare the nuances of character disposition in representing themes of loss and recovery as depicted in Anne of Green Gables by Montgomery 1908 and The Secret Garden by Burnett 1911 nbsp; By utilising the theory of theme the tripartite model deriving from the psychoanalytical theory character theory and bildungsroman it was intrinsically and extrinsically explained in regards to the representation of themes Certain psychoanalytically categorised behaviours exuded from the characters that affect their disposition towards the events they undergo throughout the story also defines their similarities and contrasts This study used the qualitative method that focused on collecting and describing written data from the source material and interpretation nbsp; The results of this study show that the representations of loss and recovery are identified in both characters and their behaviours that were psychoanalytically categorised Through this categorisation Anne and Mary s initial opposition in their dispositions gradually began to alter their perception which allowed for comparisons to be drawn for their similarities and differences < p>
Keywords: comparative study; psychoanalysis; literature; themes; novel; Anne of Green Gables; The Secret Garden